2014
DOI: 10.1021/om400691q
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydrogenase Models: The Mixed-Valence Triiron Complex [Fe3(CO)7(μ-edt)2] and Phosphine Derivatives [Fe3(CO)7–x(PPh3)x(μ-edt)2] (x = 1, 2) and [Fe3(CO)52-diphosphine)(μ-edt)2] as Proton Reduction Catalysts

Abstract: The mixed-valence triiron complexes [Fe3(CO)7–x(PPh3)x(μ-edt)2] (x = 0–2; edt = SCH2CH2S) and [Fe3(CO)5(κ2-diphosphine)(μ-edt)2] (diphosphine = dppv, dppe, dppb, dppn) have been prepared and structurally characterized. All adopt an anti arrangement of the dithiolate bridges, and PPh3 substitution occurs at the apical positions of the outer iron atoms, while the diphosphine complexes exist only in the dibasal form in both the solid state and solution. The carbonyl on the central iron atom is semibridging, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Theoretical calculations using density functional theory (level of theory B3LYP/TZVP; see Methods in the Supporting Information for details) were also performed. An analysis of the electronic structure reveals that the nature of the HOMO and the LUMO is similar to that reported previously for similar trinuclear compounds (Figure ). The HOMO can be described as a Fe–Fe bonding orbital involving the iron atoms not coordinated to the dppe ligand.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Theoretical calculations using density functional theory (level of theory B3LYP/TZVP; see Methods in the Supporting Information for details) were also performed. An analysis of the electronic structure reveals that the nature of the HOMO and the LUMO is similar to that reported previously for similar trinuclear compounds (Figure ). The HOMO can be described as a Fe–Fe bonding orbital involving the iron atoms not coordinated to the dppe ligand.…”
supporting
confidence: 85%
“…The structural determination of [Fe–Fe]-hydrogenases in the late 1990s has led during the last 15 years to a deep reinvestigation and development of the pioneering chemistry on iron carbonyl thiolate complexes developed in the 1980s . The use of well-known organometallic tools has allowed the reproduction of some chemical and structural precedents of the natural site which have contributed to a better understanding of the chemistry of the H cluster. , During the course of these studies very original side products featuring quasi-linear tri- and tetranuclear arrangements have been reported. Even if these novel polynuclear species do not model directly the H cluster, their chemistry is related. For example, it has been shown that the reduced form of the mixed-valence tetrairon cluster [Fe 4 (CO) 8 {μ 3 -(SCH 2 ) 3 CMe} 2 ], featuring a Fe I Fe II Fe II Fe I core, may be a better catalyst than the related biomimetic hexacarbonyl diiron dithiolate complexes .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 formation via proton-reduction [14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Two groups have independently studied protonreduction by the sulfide cluster [Fe 3 (CO) 9 (µ 3 -S) 2 ] (1S) [14,15] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%